Bone alignment after minimally invasive plate osteosynthesis of the tibia in dogs - Costa Junior, Jose Sergio [UNESP]; Dreibi, Rafael Manzini [UNESP]; Franco, Guilherme Galhardo; Gosuen Goncalves Dias, Luis Gustavo [UNESP]; Giuffrida, Rogerio; Minto, Bruno Watanabe [UNESP] (Univ Federal Santa Maria, 2021)
This study assessed radiographically changes in tibial alignment in the frontal and sagittal planes in dogs that underwent minimally invasive plate osteosynthesis (MIPO) without the aid of image intensifiers. Radiographs of dogs with complete non-articular tibial fractures submitted to MIPO were included and evaluated, without the aid of a transoperative image intensifier and / or an association of implants. The tibial mechanical angles (mMPTA, mMDTA, mCaPTA and mCrDTA) were measured by three evaluators. The data obtained were compared with results from previously published studies. Twenty-seven animals were included in the study. The mean and standard deviation of the angular changes were as follows: mMPTA, 2.54 degrees +/- 3.10 (-1.1 degrees to 8.7 degrees); mMDTA, 0.03 degrees +/- 0.16 (-3.44 degrees to 0.79 degrees); mCaPTA, 37 degrees +/- 4.29 (-6.23 degrees to 14.87 degrees); and mCrDTA, 8.25 degrees +/- 5.53 (-0.2 degrees to 17.28 degrees). There was a negative correlation between mCaPTA and mCrDTA. MIPO of the tibia without using image intensifiers and implant association can potentially cause angular changes, which can lead to clinically relevant deformities after bone healing.
Keywords: angular deformities; mechanical axis; MIPO; fracture